Pengembangan Media Interaktif Berbasis Canva pada Materi Pecahan dalam Meningkatkan Numerasi Matematika di SD - Aulia Rahmawati; Nurafni Nurafni (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research is to develop media based on the canva application in interactive learning that can improve numeracy math skills in grade V students in a valid and effective way. The method utilized is Research and Development (RnD) ADDIE model which contains 5 ways including analysis, design, development, implementation, and evaluation. This approach combines qualitative and quantitative methods. Qualitative data is obtained during interviews with material experts and media experts, then quantitative data is obtained during material expert validation, media expert validation, and a questionnaire of 31 fifth grade students to determine the feasibility of the media. The acquisition of material expert validation whose average is 93% at “very feasible” the acquisition of media expert validation whose average is 90% at “very feasible” and the questionnaire of students gets an average of 89.5% at “very feasible”. The effectiveness test is obtained from the n-gain test, the acquisition of the average n-gain percentage test of pretest and posttest results obtained 63.16% can be categorized as “quite effective”. The conclusion in this study is that the use of interactive learning media based on canva is very feasible and effective when improving students' math numeracy skills, then it can be used as a learning reference.